COMPREHENSIVE ANALYSIS OF ENVIRONMENTAL FACTORS CONTRIBUTING TO HIGH INFERTILITY RATES - Bander Huwaymid Alkamili, Nawaf Marzoug Alharbi, Ahmad Saad Al-Harbi, Ashwag Lafi Ali Albeladi, Hanaa Mosem Albeshri, Randa Mohamad Almwald, Zaki Abdulaziz Almaramhi, (Chelonian Research Foundation, 2022)
According to medical definitions, infertility is a condition that is present when a couple doesn't get pregnant after a year of unprotected sex in which both partners are active and sexually healthy; personal samples indicate that around 10-15% of couples are facing infertility(Kamiński et. al 2020). According to the latest WHO statistics, it is estimated that 50–80 million men and women in the world are referred to infertility cases, and one in three of them is due to male factors. Most of the men's infertility diagnoses rely on semen analysis. Human sperm's constituents are divided into two main fractions: a) density, b) appearance, and c) motility. Male infertility may be caused by multiple conditions, such as body abnormalities, hormone imbalances, lifestyle problems, psychological issues, poor sexual practices, chromosomal abnormalities, and even single gene errors. In essence, for about 70% of men who are proven to have infertility, scientists have failed to unravel their origins. Keywords: male infertility, spermatogenesis, azoospermic-obstructive azoospermia.